Hello there!
The one is asking lot of hard work and I don't know how to write the quadratic formula so I can't show the work for this one.
The answer is : two solutions
#2
Number two is easy to show my work
0 = 3x² + 18x + 27
-3x² - 18x - 27 = 0
Now all we have to do is factorize
-3(x + 3)(x + 3) = 0
Now set each factors equal to 0
x + 3 = 0 or x + 3 = 0
x = - 3
The correct option is A - One solution
A+ Guaranteed! If you have further question or misunderstand the steps please feel free to ask.
Have a nice day!